Detection and quantification of splicing variants of Hd3a gene in oil palm - Aqwin Polosoro; Wening Enggarini; Kusumawaty Kusumanegara; Toto Hadiarto; Miftahudin Miftahudin; Ence Darmo Jaya Supena (Indonesian Journal of Biotechnology, 2024)
Alternative splicing is a complex process that contributes to the generation of diverse mRNA and protein isoforms, including in oil palm (Elaeis guineensis). Despite their importance, many functions of alternative splicing genes remain poorly characterized. This study aims to investigate splicing variants of gene encoding Heading date 3a in E. guineensis (EgHd3a) using the GenBank database and ClustalW algorithm. To ensure the data accuracy and reliability of design isoform‐ specific primers, special emphasis is given to primer design techniques and validation using polymerase chain reaction (PCR) and quantitative real‐time (qRT)‐PCR analysis. The designed primers demonstrated high specificity and discrimination between mRNA specimens. Nucleotide variations at the 3’‐end influenced the specificity of primers with the addition of GC composition. Furthermore, qRT‐PCR analysis revealed a strong correlation between Ct values and gene concentration for the isoforms which indicates a reliable amplification of EgHd3a. Although two isoforms, Hd3a‐X2 and Hd3a‐X3, showed slightly higher than acceptable PCR efficiency values, caution is advised to prevent non‐specific amplification. Despite the challenge posed by the limitation of primer positioning due to alternative splicing, the chosen primer proved optimal for analysis. This study highlights the importance of considering alternative splicing in gene quantification experiments and provides insights into the critical steps, methods, and quality control measures necessary for accurately detecting alternative splicing events, contributing to understanding this complex biological process.